PENGARUH PERHATIAN ORANG TUA DAN STRATEGI MENGAJAR GURU TERHADAP PERILAKU BELAJAR PAI DI MI MA'ARIF - Maryam Jamilah Yanayirtika (Edusoshum : Journal of Islamic Education and Social Humanities, 2021)
This study aims to determine whether there is an effect of parental attention and teacher teaching strategies on Islamic education learning behavior at MI Ma'arif Bulurejo. The population in this study were 204 students, while the sample used was 40 students in grade V (five). Data analysis techniques in the form of percentages and statistical analysis of multiple linear regression using the help of the SPSS program for windows release version 21.0. The results showed that: 1) Parents' attention has a positive and significant influence on the learning behavior of PAI. The regression coefficient value is 0.288 with a probability level of 0.034 which is smaller than the significance level of 0.05, and the amount of variable contribution is 26.11%. 2) The teaching strategy of teachers has a positive and significant influence on PAI learning behavior, the regression coefficient value is 0.434 with a probability level of 0.029 which is smaller than the significance level of 0.05, and the amount of variable contribution is 26.6% 3) Parents' attention and teacher teaching strategies together has a positive and significant influence on the learning behavior of PAI, the value of F count is 10.020 with a probability level of 0.000 smaller than the significance level of 0.05, and the coefficient of determination is 35.1%, while the remaining 64.9% is influenced by other factors